Comparing the normalised and 2PL IRT scoring methods on multi-form examinations. (15th December 2021) - Xie, Aolin; Chiu, Ting-Wei; Chen, Keyu; Camilli, Gregory
This study compared candidates' scores based on the normalised model and the two-parameter item response theory (2PL IRT) model using simulated multi-form exam data. Candidates' calculated scores, rankings, qualification status and score ties from the two models were compared with their true values. The results suggest that the 2PL IRT model outperformed the normalised model when the candidate ability distributions varied across forms. It was found that candidate scores based on the 2PL model were more closely related to the true scores. The qualification status of candidates belonging to the top 10% group were more accurately classified by the 2PL model than the normalised model when group abilities differed.